Does insider trading explain price run‐up ahead of takeover announcements?. (14th November 2012) - Aspris, Angelo; Foley, Sean; Frino, Alex; Faff, Robert
Abstract This study empirically examines the impact of changes in substantial shareholdings ahead of 450 Australian takeover offers between the years 2000 and 2009. Previous studies have attributed a significant proportion of the price run‐up effect in takeover targets to insider‐trading behaviour. This study examines the contribution of a broad range of public information sources that are known to typically generate market anticipation, including the acquisition of toeholds ahead of takeover announcements. Our findings show no significant pre‐bid run‐up for takeover targets after considering these sources. We conclude from these results that previous findings attributing pre‐bid share price run‐up to illegal insider trading may overstate the existence of such conduct.